N1 and P1 Components Associate With Visuospatial-Executive and Language Functions in Normosmic Parkinson’s Disease: An Event-Related Potential Study - Lin, Yi-Qi; Cui, Shi-Shuang; Du, Juan-Juan; Li, Gen; He, Yi-Xi; Zhang, Ping-Chen; Fu, Yang; Huang, Pei; Gao, Chao; Li, Bin-Yin; Chen, Sheng-Di (Frontiers in Aging Neuroscience, 2019)
Background: Hyposmia is one of the most important clinical markers of Parkinson’s disease (PD) with a prevalence ranging from 50% to 96% of PD patients. A significant association was found between hyposmia and cognitive impairment of PD. However, there were no reports of event-related potentials (ERP) performance in PD patients with and without hyposmia for cognitive functions assessment. Purpose: The aim of our study was to compare ERP performance and its association with cognitive domains between PD with and without hyposmia. Methods: Olfactory functions were assessed by Sniffin' Sticks test-16 (SS-16). Twenty-four subjects were included in PD with hyposmia group and nineteen were in PD without hyposmia group. ERP measures were recorded during a delayed match to sample (DMS) task with Chinese characters. The parameters of ERP components including N1, N2, P1, P2 and P3 in retrieval epoch were compared between the two groups and the correlation between ERP results and MOCA item score was also analyzed. Results: No significant difference was found in ERP performance between PD with and without hyposmia. Among all participants, N1 latency was significantly negatively related to visuospatial-executive item score of Montreal Cognitive Assessment (MOCA) (rs =-0.381, P=0.012) and P1 amplitude was positively associated with language item score of MOCA (rs =0.302, P=0.049). Within the normosmic group, a significant association was found between N1 latency and visuospatial-executive item score (rs =-0.619, P=0.005) and there was also a correlation between language score and P1 amplitude (rs =0.537, P=0.018). In the hyposmic group, only a significant correlation was found between N1 latency and clock drawing test performance (rs =-0.413, P=0.045) rather than visuospatial-executive item score. Furthermore, SS-16 score was not found to be significantly associated with either visuospatial-executive or language item score of MOCA. Conclusion: No significant difference was found in ERP components between PD with and without hyposmia. N1 latency and P1 amplitude were respectively associated with visuospatial-executive and language functions in the normosmic group while in the hyposmic group, only a significant correlation was found between N1 latency and clock drawing test performance rather than visuospatial-executive item score in MOCA.